Burden and disparities in cardiovascular mortality rates associated with obesity prevalence in United States: county-level analysis from 2010 to 2019. (3rd October 2022) - Abohashem, S; Sayed, A; Aldosoky, W; Diab, M; Mir, T; Sattar, Y; Dar, T
Abstract: Background: Obesity is a grave public health threat linked to high morbidity and mortality rates. A significant rise in obesity rates amongst U.S. adults and worldwide has been observed in recent decades. Although associations between obesity and cardiovascular mortality (CVM) are well-known, impact and disparities in CVM attributable to obesity at a nationwide community level, aren't well defined. Purpose: At county level, we sought to evaluate the independent impact of adult obesity on CVM in overall population and within different age, sex, and race/ethnic subgroups. Methods: Age-adjusted CVM rates (ACVM) between 2010 to 2019, were obtained using Wide-ranging Online Data for Epidemiologic Research tool of Center for Disease Control (CDC). Using the Behavioral risk Factors Surveillance System (BRFSS), obesity rates per county was assessed as the percentage of adult population (age ≥20) that reports a body mass index ≥30 kg/m 2 . BRFSS, CDC Diabetes Interactive Atlas, census population estimates, environmental public health network and health county ranking project databases, were utilized to acquire county data of demographics, CV risk, socio-environmental, and health care access factors. Poisson multivariate generalized linear mixed models were employed to assess incidence rate ratios (IRR) of ACVM associated with obesity rates. To evaluate the absolute impact of obesity on ACVM, additional yearly deaths (AYD) per 100, 000 individuals were calculated. All study analysis were weighted for the relevant county baseline population. Results: Among 307, 045, 647 residents (50% women, 12% non-Hispanic blacks, 24% aged 45–64) lived at 2904 US counties in 2010, total 8, 157, 571 (2.7%) CV deaths occurred between 2010–2019. In fully adjusted model*, high obesity rates significantly associated with high ACVM (IRR: 1.015; 95% CI: 1.008 to 1.022), that translated to 3.5 AYD per 100, 000 individuals. In a subgroup analysis, obesity rates associated with a relatively higher ACVM among overall middle aged adults [45 to 64] (IRR: 1.028; 95% CI: 1.018 to 1.037) versus elderly [≥65] (IRR: 1.013; 95% CI: 1.006 to 1.020), and in males (IRR: 1.018; 95% CI: 1.010 to 1.026) versus females (IRR: 1.014; 95% CI: 1.006 to 1.022), and in Hispanics (IRR: 1.035; 95% CI: 1.005 to 1.065) versus non-Hispanic Whites (IRR: 1.020; 95% CI: 1.012 to 1.027). Interestingly, middle aged adults had higher ACVM IRRs as compared to elderly, among males (IRR: 1.022), females (IRR: 1.039), and non-Hispanic Whites (IRR: 1.044) (Figure). Conclusions: Obesity prevalence is independently associated with high ACVM among different age, sex, and race/ethnic groups, and this impact is most pronounced in Hispanics and the middle-aged group of females and non-Hispanic Whites. More research is needed to further uncover the mechanisms leading to these observations a long with community-level interventions to reduce the burden of this ongoing epidemic, in overall and most impacted population groups. Funding Acknowledgement: Type of funding sources: None.